INVESTIGATION OF COOLING CAPACITY OF THE COOLER FLOODED STREAM - E. I. Marukovich; V. Ju. Stetsenko; R. V. Konovalov (Литьë и металлургия, 2011)
It is shown that the maximum cooling ability of the flooded stream with diameter of 3,5 mm at input pressure of the cooler 0,1–0, 25 µPa is reached at distance between the stream nozzle and the cooled surface, equal 8 mm.